2020
DOI: 10.3390/ijerph17041157
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Liquid Chromatography Mass Spectrometry and Enzyme-Linked Immunosorbent Assay Methods to Measure Salivary Cotinine Levels in Ill Children

Abstract: Objective: Cotinine is the preferred biomarker to validate levels of tobacco smoke exposure (TSE) in children. Compared to enzyme-linked immunosorbent assay methods (ELISA) for quantifying cotinine in saliva, the use of liquid chromatography tandem mass spectrometry (LC-MS/MS) has higher sensitivity and specificity to measure very low levels of TSE. We sought to compare LC-MS/MS and ELISA measures of cotinine in saliva samples from children overall and the associations of these measures with demographics and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Saliva was tested for cotinine, a measure of recent TSE [36] using enzyme-linked immunosorbent assay (ELISA) techniques by Salimetrics LLC [23] (78.2% of T0 and all T1 and T2 samples; level of detection (LOD) = 0.15 ng/mL) or by liquid chromatography tandem mass spectrometry (LC-MS/MS) with isotope dilution (21.9% of T0 and none of the T1 and T2 samples; LOD = 0.1 ng/mL) [37]. A prior publication indicates that ELISA is a cost-effective alternative to LC-MS/MS for detecting TSE to classify children into highly exposed versus not exposed to tobacco smoke [38]. Cotinine levels less than LOD were replaced with LOD/ √ 2.…”
Section: Child Measures Saliva Collection and Analysismentioning
confidence: 99%
“…Saliva was tested for cotinine, a measure of recent TSE [36] using enzyme-linked immunosorbent assay (ELISA) techniques by Salimetrics LLC [23] (78.2% of T0 and all T1 and T2 samples; level of detection (LOD) = 0.15 ng/mL) or by liquid chromatography tandem mass spectrometry (LC-MS/MS) with isotope dilution (21.9% of T0 and none of the T1 and T2 samples; LOD = 0.1 ng/mL) [37]. A prior publication indicates that ELISA is a cost-effective alternative to LC-MS/MS for detecting TSE to classify children into highly exposed versus not exposed to tobacco smoke [38]. Cotinine levels less than LOD were replaced with LOD/ √ 2.…”
Section: Child Measures Saliva Collection and Analysismentioning
confidence: 99%
“…Consistent with our hypothesis, we observed higher levels of COT and 3HC + COT sums, but lower 3HC/COT ratio levels in children who were non-Hispanic Black compared to children who were non-Hispanic White race/ethnicity, independent of other child sociodemographic and TSE patterns. Regarding COT, other prior research has also found that COT levels are higher in children who are of Black race and who are younger [2,7,32]. These higher COT levels may be due to slower metabolism secondary to genetic polymorphisms in the CYP2A6 gene in these child groups [4,[11][12][13].…”
Section: Discussionmentioning
confidence: 85%
“…Cotinine (COT) is a nicotine metabolite and it is a commonly used TSE biomarker [4]. Prior research indicates that up to 31% of children who live with smokers who seek care in emergency settings have high biochemically confirmed TSE levels that are equivalent to that of active smokers [5][6][7][8]. COT is measurable in the urine, saliva, blood, hair, and nails of exposed children who live with smokers and nonsmokers [3], and it has a half-life of approximately 16 h [5,9]; thus, COT levels reflect recent TSE.…”
Section: Introductionmentioning
confidence: 99%
“…8 Research indicates that all children of cigarette smokers, even those whose parents enforce smoking bans, have detectable hand nicotine and cotinine with higher levels in younger children and those exposed to more cigarettes. 5,8,[10][11][12][13] Whereas the nicotine concentration in cigars compared to cigarettes is similar, the total tobacco content in cigars is higher than cigarettes, and the smoke emissions and TSE patterns from cigars and cigarettes may vary. 14 TSE biomarker levels differ by cigar type and use patterns and the use of other tobacco products (eg, dual-or poly-use with cigars, cigarettes, and/or marijuana).…”
mentioning
confidence: 99%